2002
DOI: 10.1289/ehp.110-1241197
|View full text |Cite
|
Sign up to set email alerts
|

Cancer risk assessment, indicators, and guidelines for polycyclic aromatic hydrocarbons in the ambient air.

Abstract: Polycyclic aromatic hydrocarbons (PAHs) are formed during incomplete combustion. Domestic wood burning and road traffic are the major sources of PAHs in Sweden. In Stockholm, the sum of 14 different PAHs is 100-200 ng/m(3) at the street-level site, the most abundant being phenanthrene. Benzo[a]pyrene (B[a]P) varies between 1 and 2 ng/m(3). Exposure to PAH-containing substances increases the risk of cancer in humans. The carcinogenicity of PAHs is associated with the complexity of the molecule, i.e., increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
661
3
14

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 741 publications
(695 citation statements)
references
References 176 publications
9
661
3
14
Order By: Relevance
“…Some PAHs are genotoxic and bind to DNA, while others have tumor promoting effects [Boström et al, 2002]. In this study, we showed that soil fractions from industrially contaminated sites, containing complex mixtures of PAHs and related compounds (e.g., oxy-PAHs), exhibited soilspecific patterns of DNA damage signaling proteins and exhibited signs of interactions between different PAHs.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Some PAHs are genotoxic and bind to DNA, while others have tumor promoting effects [Boström et al, 2002]. In this study, we showed that soil fractions from industrially contaminated sites, containing complex mixtures of PAHs and related compounds (e.g., oxy-PAHs), exhibited soilspecific patterns of DNA damage signaling proteins and exhibited signs of interactions between different PAHs.…”
Section: Discussionmentioning
confidence: 62%
“…Benzo [a]pyrene is often used as an indicator of carcinogenic PAHs in complex mixtures [Boström et al, 2002]. However, animal studies have shown that the BP indicator may reflect as little as 20% of the cancer potency of such mixtures, and may thus underestimate the risk [Gaylor et al, 2000].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAH bind to cytosolic receptors and may therefore affect cell growth and differentiation [Bayram et al, 1998]. Some PAHs are human mutagens and carcinogens [Bostrom et al, 2002]. Since PAHs occurred in all three toner-powder samples (Table II), we conclude that these compounds are responsible for the genotoxic effects determined by the comet and CB-MNvit assays.…”
Section: Chemical Compositionmentioning
confidence: 92%
“…Particulate organic compounds and chiefly polycyclic aromatic hydrocarbons (PAHs) are produced by incomplete combustion processes and some of those are known carcinogenic species, while others are suspected of being carcinogenic (Bostrom et al, 2002). Another group that has gained interest in recent years is metals.…”
Section: Health Effects Of Aerosolsmentioning
confidence: 99%